The strategic importance of Bolbitine(Civilization study) - Nancy Hussam Mahmoud (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2020)
The site of the city of Bolbitine, whose ruins are located in the south of the current city of Rosetta, on the mouth of the western branch of the Nile (Rosetta branch), was a city populated throughout the history of ancient Egypt, and since the time of King Mina, it was known as Ghetto, and Rekhyt were the ancient inhabitants of the Delta before the unit. Politics between the South and the North in the First Dynasty, and they were called the best people (Rakhetto), had resisted King Mina as he crawled to unite the North and the South. In the Greek era, it was called Bolbitine, and in the Ptolemaic era, it became the Coptic name "Rashet" and later Rosetta. The research deals with the strategic importance of Bolbitine (Rosetta), which resulted from its occurrence on the mouth of the Polytechnic branch (the Rosetta branch), and what was exposed to the northern coast of the Delta was a reason for fortifying civilized sites along the Mediterranean coast, and at the entrances to the Nile branches, especially the Poleptine branch (Rosetta branch). This has had a great impact on increasing interest in its fortification, especially in the era of the New Kingdom (1575-1085 BC). Where King Merneptah built a castle at the mouth of the Nile and King Ramses III completed its construction, which is the castle that has remained until now and was renovated in the Mamluk era as Qaitbay Castle.